ELEIÇÃO PARA DIRETORES EM DIADEMA: ENTRAVES E AVANÇOS - Almeida, Simone de Oliveira (2013)
The goal of this research is to investigate the trajectory of the election for directors in the city of Diadema, being that it is not effected by Public Contest. Also investigate the successes and the possible obstacles that occur in this process, considered democratic. Parents, students, community, employees and others are involved in a participative manner at the time of the election, as it is with the vote of the social actors of the school that if you elect those who will represent the school unit for three years or more. Will this process ensures really democracy within the school spaces? To do so, will be made a documentary research, with official documents, based on the laws that deal with the subject, as well as the Pedagogic political project of schools and other existing documents. Use previous work on the topic, together with authors such as Vitor Paro, Heloisa Luck, Juan Bordenave, Maria Leila Alves and Décio Saes.